Barriers and limitations of employment in desistance: exploring the experiences of men leaving prison in Aotearoa New Zealand - Mills, Alice (International journal of offender therapy and comparative criminology, 2026)
Through narrative interviews with 16 men leaving prison in Aotearoa New Zealand, the current research contributes to the literature on the role of employment in desistance by emphasising some of the barriers to (or limitations of) its desisting effects. In particular, the study emphasises structural constraints in the colonial setting of Aotearoa New Zealand, which can prevent Indigenous Māori men from obtaining stable, rewarding work. The study emphasises how different types of work and work environments can have varying effects on desistance, with some even encouraging reoffending and needing to be ‘knifed off’ to support the men’s desistance journeys. It is argued that those leaving prison should not be encouraged into ‘any’ job, but rather work which provides adequate remuneration, satisfaction, and opportunities to build a positive identity to foster desistance. This may require the state, particularly the Department of Corrections, and employers to facilitate opportunities into suitable employment.